Efek Larutan Asam Terhadap Kuat Tekan dan Penyerapan Mortar dengan Bahan Tambah Fly Ash - Mufti Amir Sultan; Raudha Hakim; Kurniawan Kurniawan (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Mortar is a mixture consisting of fine aggregate and adhesive. This mortar serves as a filler or binder in the constituent parts of a construction, both non-structural and structural. In this study, the test object measuring 5x5x5 cm was used by using fly ash added from the PLTU Rum by 20% of the cement weight. This study aims to clarify the use of fly ash from PLTU Rum as an additive in mortar mixtures. The test object is immersed in an acid solution with a concentration of 2%, the duration of immersion is 30, 60 and 90 days. The addition of fly ash to the mortar mixture can increase the compressive strength by 23.32%. The longer the contact with the acid solution will decrease the compressive strength and increase the absorption of the mortar.